Electrode, preparation method thereof and solid-state battery

By using current collectors and electrodes covering the carbon nanotube layer in all-solid-state battery electrodes, the problem of high expansion rate of lithium metal is solved and the battery performance and life is improved.

CN119627040APending Publication Date: 2025-03-14FARASIS TECH (GANZHOU) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411606613.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In all-solid-state battery design, the high volume expansion rate of lithium metal leads to limited battery performance and life. How to effectively limit the expansion of lithium metal through electrodes has become a core technical problem.

Method used

A current collector and an electrode covering the carbon nanotube layer of the current collector are used, and a catalyst is arranged on the bottom and top portions of the carbon nanotubes. The carbon nanotubes are grown by chemical vapor deposition method to prepare a carbon nanotube electrode with a catalyst.

Benefits of technology

By uniformly deposition of lithium ions, local overpotential and lithium evolution phenomena are avoided, and the amount of lithium deposition does not exceed the maximum deposition capacity of carbon nanotubes, so that the electrode does not expand or contract during charging and discharging, effectively limiting the expansion of lithium metal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627040A_ABST
    Figure CN119627040A_ABST
Patent Text Reader

Abstract

The invention discloses an electrode and a preparation method thereof and a solid-state battery, the electrode comprises a current collector and a carbon nanotube layer covering the current collector, and catalysts are distributed at the bottom and the top of the carbon nanotube; when the electrode in the technical scheme is applied to the battery, as the catalyst is arranged at the bottom and the top of the carbon nano tube, lithium metal can be synergistically induced to be uniformly deposited on the surface and the bottom of the carbon nano tube electrode, and when lithium ions are uniformly distributed on the surface and inside of the electrode (inside and among the carbon nano tube), the condition that the local lithium ion concentration is too high does not occur; the generation of local overpotential can be avoided through uniform deposition, so that lithium precipitation is prevented; meanwhile, by designing and controlling the deposition amount of lithium not to exceed the maximum in-tube and inter-tube deposition capacity of the carbon nanotubes, the whole electrode is free of expansion and shrinkage in the charging and discharging process, and lithium metal expansion is effectively limited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to an electrode and a preparation method thereof, and a solid-state battery. Background Art

[0002] As the current mainstream energy storage device, the internal structure and working principle of traditional liquid batteries are relatively mature. However, liquid batteries have inherent limitations in terms of energy density and cycle life, which is mainly attributed to the incompatibility of liquid electrolytes and lithium metal anodes. Specifically, liquid electrolytes are chemically difficult to coexist stably with lithium metal, resulting in rapid performance degradation of the battery during the charge and discharge cycle, which severely limits the application of lithium metal anodes in liquid batteries. As a negative electrode material with high energy density, lithium metal has a theoretical energy density of up to 3860mAh / g, far exceeding other existing negative electrode materials. Therefore, if the lithium metal anode can be effectively utilized, the energy density and endurance of the battery will be greatly improved.

[0003] In order to overcome this bottleneck of liquid batteries, researchers began to explore all-solid-state battery technology. The core innovation of all-solid-state batteries is the use of solid-state electrolytes to replace traditional liquid electrolytes and polymer separators. Solid-state electrolytes, due to their unique wide voltage window characteristics (wide voltage window characteristics refer to the ability of solid electrolytes to remain stable over a large voltage range without decomposition or significant performance degradation, and the window refers to the voltage range in which the electrolyte can work safely and effectively), have successfully solved the problem of incompatibility between liquid electrolytes and lithium metal, making the use of lithium metal negative electrodes in all-solid-state batteries possible. This breakthrough has opened up a new way to improve battery energy density and is expected to promote a qualitative leap in battery technology.

[0004] However, in the commercial application of all-solid-state battery technology, although solid-state electrolytes make it possible to use lithium metal negative electrodes, the extremely high volume expansion rate of lithium metal during the charging and discharging process has become a key factor restricting the performance and life of all-solid-state batteries. The high energy density of lithium metal is accompanied by significant volume changes, which not only leads to drastic fluctuations in the overall volume of the battery, but may also cause the deterioration of the interface structure between the electrolyte and lithium metal, which in turn seriously affects the cycle stability and service life of the battery. Therefore, in the design of high-energy-density solid-state batteries, how to effectively limit the expansion of lithium metal through electrodes has become a core technical problem that needs to be solved urgently. Summary of the invention

[0005] The main purpose of the present invention is to provide an electrode and a preparation method thereof and a solid-state battery, aiming to solve the technical problem of how to effectively limit the expansion of lithium metal through electrodes in the existing high-energy density solid-state battery design.

[0006] In order to achieve the above objective, the first aspect of the present invention provides an electrode, comprising a current collector and a carbon nanotube layer covering the current collector, wherein a catalyst is distributed at the bottom and top of the carbon nanotube.

[0007] Furthermore, the current collector is made of metal.

[0008] Furthermore, the catalyst comprises one or more selected from silver and silver-containing complexes.

[0009] Furthermore, the carbon nanotubes are one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes and modified carbon nanotubes.

[0010] A second aspect of the present invention provides a method for preparing an electrode, which is used to prepare any of the electrodes described above, comprising the following steps:

[0011] S1: coating the catalyst on the current collector;

[0012] S2: placing the coated current collector in a fluidized bed for fluidization;

[0013] S3: introducing a carbon source into the fluidized bed to grow carbon nanotubes by chemical vapor deposition to produce the electrode.

[0014] Furthermore, the carbon source is one or more combinations of carbon monoxide, carbon dioxide, ethylene, acetylene, methane and propylene gases.

[0015] Furthermore, the chemical vapor deposition method is a direct current electrodeposition method or a pulse electrodeposition method.

[0016] A third aspect of the present invention provides a solid-state battery, comprising any one of the electrodes described above as a negative electrode.

[0017] Furthermore, the electrolyte of the solid-state battery is a solid electrolyte.

[0018] Furthermore, the negative electrode also includes a negative electrode active material, and the negative electrode active material is metallic lithium.

[0019] Beneficial effects:

[0020] Compared with the prior art, an electrode of the present invention comprises a current collector and a carbon nanotube layer covering the current collector, wherein the bottom and top of the carbon nanotube are distributed with a catalyst; when the electrode in the technical solution is applied to a battery, since the catalyst is at the bottom and top of the carbon nanotube, it can synergistically induce the uniform deposition of lithium metal on the surface and bottom of the carbon nanotube electrode. When the lithium ions are uniformly distributed on the surface and inside of the electrode (inside and between the carbon nanotubes), there will be no excessive concentration of local lithium ions. During the lithium ion charging process, lithium ions need to overcome a certain potential difference to be deposited on the negative electrode. If the lithium ions are not uniformly deposited, the lithium ion concentration in the local area is too high, which will cause the potential difference in the area to be too large, i.e., local overpotential. The local overpotential will cause the lithium ions to be excessively deposited in the area, forming the precipitation of metallic lithium, i.e., the lithium precipitation phenomenon. Uniform deposition can avoid the generation of local overpotential, thereby preventing lithium precipitation; at the same time, by designing and controlling the deposition amount of lithium not to exceed the maximum deposition capacity of the carbon nanotubes in the tubes and between the tubes, the entire electrode is free of expansion and contraction during the charging and discharging process, effectively limiting the expansion of lithium metal.

[0021] Compared with the prior art, the present invention provides a method for preparing an electrode. After coating the catalyst on a current collector, the carbon nanotubes are grown by chemical vapor deposition in a fluidized bed. During the fluidization process, the catalyst migrates to a certain extent as the gas flows and the reaction proceeds, so that the catalyst is distributed on the surface of the current collector (the bottom of the carbon nanotubes) and the top of the growing carbon nanotubes. During the growth of the carbon nanotubes, a portion of the carbon nanotubes starts to grow from the surface of the current collector. The catalyst on the surface of the current collector serves as the starting point of the reaction, guiding the carbon source gas to decompose and form carbon nanotubes. When the carbon nanotubes grow on the surface of the current collector, a portion of them moves toward the top of the growing carbon nanotubes. The carbon nanotubes grow inside the current collector to be firmly attached to the current collector without the need for additional binders, further reducing the use of materials and lowering costs. At the same time, a portion of the carbon nanotubes grow through the catalyst on the top, so that the catalyst also appears on the top of the carbon nanotubes (electrode surface) to make an electrode. This method eliminates the need for traditional stirring and coating steps, reduces costs, and in the process of preparing the electrode, the length of the carbon nanotubes can be adjusted by adjusting the time of vapor deposition to adjust the growth length of the carbon nanotubes, and the density of the carbon nanotubes can be adjusted by the coating density of the catalyst, so that batteries with various energy densities and thicknesses can be flexibly designed.

[0022] Compared with the prior art, a solid-state battery of the present application includes the above-mentioned electrode. It is understandable that the solid-state battery of the present application can have all the technical features and beneficial effects of the above-mentioned electrode, which will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a schematic diagram of a copper foil current collector with a silver-containing catalyst on its surface in Example 1 of the present invention;

[0024] Figure 2 This is a schematic diagram of in-situ generation of carbon nanotubes in Example 1 of the present invention;

[0025] Figure 3 This is a schematic diagram of the state of the in-situ grown carbon nanotube negative electrode after lithium insertion in Example 1 of the present invention;

[0026] Figure 4 This is a flow chart of the preparation of the in-situ grown electrode in Example 1 of the present invention.

[0027] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0028] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.

[0029] See also Figures 1 to 3 An embodiment of the present invention provides an electrode, including a current collector and a carbon nanotube layer covering the current collector, wherein catalysts are distributed at the bottom and top of the carbon nanotubes, and the current collector includes a metal material.

[0030] In this embodiment, the current collector plays a supporting role. The carbon nanotube layer is covered on the current collector, and catalysts are distributed at the bottom (the part in contact with the current collector) and the top of the carbon nanotubes to induce lithium ion deposition. The current collector includes a metal material with good electrical conductivity and mechanical properties, which can provide a stable electron transmission channel and physical support for the electrode. Exemplary, it can be copper foil or aluminum foil. Copper foil is preferred in this application. In this application, the electrode is prepared by in-situ growth. In-situ growth refers to a process in which the reactants react directly in situ on the substrate on a specific substrate surface to generate a target product.

[0031] It should be noted that during the lithium ion charging process, lithium ions need to overcome a certain potential difference before they can be deposited on the negative electrode. If the lithium ions are not deposited uniformly, the lithium ion concentration in the local area is too high, which will cause the potential difference in the area to be too large, that is, the local overpotential. The local overpotential will cause the lithium ions to be excessively deposited in the area, forming the precipitation of metallic lithium, which is the lithium precipitation phenomenon. The bottom and top of the carbon nanotubes in this application are the opposite ends relative to the arrangement or growth direction of the carbon nanotubes on the current collector. The bottom refers to the part of the carbon nanotubes that is in direct contact with the current collector or close to the current collector, and the top refers to the part of the carbon nanotubes that is away from the current collector and relatively extends or protrudes.

[0032] In the above embodiment, when the electrode is applied to a battery, since the catalyst is at the bottom and top of the carbon nanotube, it can synergistically induce the lithium ions to be uniformly deposited on the surface and bottom of the carbon nanotube electrode. When the lithium ions are evenly distributed on the surface and inside of the electrode (inside and between the carbon nanotubes), there will be no local excessive lithium ion concentration, and uniform deposition can avoid the generation of local overpotential, thereby preventing lithium precipitation. At the same time, by designing and controlling the amount of lithium deposition not to exceed the maximum deposition capacity inside and between the carbon nanotubes, the entire electrode does not expand or contract during the charge and discharge process, effectively limiting the expansion of lithium metal.

[0033] In one embodiment, the catalyst comprises one or more selected from silver and a silver-containing complex.

[0034] In the present embodiment, silver has good catalytic activity, can effectively reduce the activation energy of the reaction, and promote the growth of carbon nanotubes. It has high chemical stability, is not easy to react chemically under the working environment of the battery (such as contact with solid electrolyte and charging and discharging process), can ensure its own stable performance, and continuously play a catalytic role. At the same time, silver has a guiding effect on the deposition of lithium ions, which can make lithium ions deposit evenly on the surface and bottom of the negative electrode of the carbon nanotube, avoiding the phenomenon of lithium precipitation. Iron has a variety of valence states and can participate in a variety of redox reactions to promote the growth of carbon nanotubes. For example, in the process of chemical vapor deposition, iron can adjust the reaction process by changing its own valence state. The cost of iron is relatively low, but the chemical stability of iron is not as stable as silver, and it is easy to react with oxidation, etc. Therefore, in order to make up for the deficiency of iron catalysts and reduce the cost of silver catalysts, the silver-containing complex of the present application can be a silver-based iron catalyst. Cobalt has a unique electronic structure, which enables it to provide active sites in the catalytic reaction and promote the growth of carbon nanotubes. Cobalt can form a specific adsorption state with the carbon source gas, which is conducive to the decomposition of gas molecules and the formation of carbon nanotubes. In terms of battery applications, cobalt can improve the electrochemical properties of electrodes to a certain extent, and enhance the conductivity and ion transport capacity of electrodes. However, cobalt resources are relatively scarce and expensive, and the cost of using it alone is higher than that of silver. In order to reduce the cost of the catalyst, the silver-containing composite of the present application can also be a silver-based cobalt catalyst. Nickel is a common catalyst that can accelerate chemical reactions during the growth of carbon nanotubes. The catalytic activity of nickel stems from the electronic structure and chemical adsorption characteristics of its surface atoms. It can adsorb carbon source gases and promote their decomposition. In battery electrodes, nickel helps to improve the structural stability and conductivity of electrodes. However, nickel may undergo corrosion and other reactions in certain electrolyte environments, affecting its long-term stability. Therefore, in order to ensure the stability of the catalyst, the silver-containing composite of the present application can also be a silver-based nickel catalyst. Since the silver-containing composite catalyst is compatible with some defects of its composite material compared to the silver catalyst, the present application preferably uses silver as a catalyst.

[0035] In one embodiment, the carbon nanotubes are one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes and modified carbon nanotubes.

[0036] In this embodiment, the single-walled carbon nanotube is a seamless tubular structure formed by curling a layer of graphene sheets; the multi-walled carbon nanotube is formed by nesting multiple concentric graphene tubes; the modified carbon nanotube is obtained by chemically or physically treating ordinary carbon nanotubes, introducing specific functional groups or changing their surface properties. For example, functional groups such as hydroxyl and carboxyl groups can be introduced on the surface of carbon nanotubes by surface oxidation treatment, or the electronic structure and properties of carbon nanotubes can be changed by doping with other elements. In the preparation of in-situ growth electrodes, one or more combinations of single-walled carbon nanotubes, multi-walled carbon nanotubes and modified carbon nanotubes can be selected. Different types of carbon nanotubes can play a synergistic role.

[0037] In the above embodiment, when the carbon source is introduced into the fluidized bed in the step of preparing the electrode, the mixed growth of different carbon nanotubes can be achieved by controlling the type and order of the carbon source. A carbon source gas that is conducive to the growth of single-walled carbon nanotubes is introduced first, and then a carbon source suitable for the growth of multi-walled carbon nanotubes is introduced after a certain period of time, and a gas or precursor that can modify the carbon nanotubes is added at the same time, thereby achieving a combination of multiple carbon nanotubes in the in-situ growth process.

[0038] See also Figure 4 Combined with Figures 1 to 3 Another embodiment of the present invention provides a method for preparing an electrode, which is used to prepare any of the electrodes described above, comprising the following steps:

[0039] S1: coating the catalyst on the metal current collector;

[0040] S2: placing the coated current collector in a fluidized bed for fluidization;

[0041] S3: introducing a carbon source into the fluidized bed to grow carbon nanotubes by chemical vapor deposition to produce the electrode.

[0042] In this embodiment, the metal material is used as the current collector of the electrode to provide physical support for the subsequent growth of carbon nanotubes. The catalyst is the key factor in the growth of carbon nanotubes, which will guide the growth process of carbon nanotubes. Through the coating operation, the catalyst is evenly distributed on the surface of the metal current collector to provide active sites for the subsequent chemical vapor deposition reaction. According to the properties of the selected catalyst, such as silver, iron, cobalt, and nickel, these metals have catalytic activity and can reduce the activation energy of the carbon nanotube growth reaction. For example, the surface of silver can adsorb carbon source gas molecules. When the catalyst is coated on the metal current collector, the active sites on its surface can interact with the carbon source gas that is about to be introduced.

[0043] In the above embodiments, the main purpose of the fluidization operation is to put the current collector coated with the catalyst in a good reaction state. The fluidized bed allows the catalyst particles to be suspended in the airflow, so that the current collector is in full contact with the reaction gas. This ensures that when the carbon source gas is subsequently introduced, the reaction between the catalyst and the carbon source gas is more uniform, avoiding situations where the local reaction is too intense or the reaction is incomplete. At the same time, during the catalyst fluidization process, the catalyst will migrate to a certain extent as the gas flows and the reaction proceeds, so that the catalyst is distributed on the surface of the current collector (the bottom of the carbon nanotubes) and on the top of the growing carbon nanotubes, such as Figure 2 As shown, during the growth process of carbon nanotubes, a portion of the carbon nanotubes starts to grow from the surface of the current collector, and the catalyst on the surface of the current collector serves as the starting point of the reaction, guiding the carbon source gas to decompose and form carbon nanotubes; at the same time, another portion of the carbon nanotubes grows through the catalyst on the top, so that the catalyst also appears on the top of the carbon nanotubes (electrode surface) to make an in-situ grown electrode.

[0044] It should be noted that the appendix to this application Figure 2 Only the growth of carbon nanotubes on one side of the current collector is shown. It is understandable that carbon nanotubes can also be grown on the other side at the same time.

[0045] In the above embodiment, by introducing carbon source gas, carbon nanotubes are grown on a current collector coated with a catalyst using chemical vapor deposition, thereby forming an electrode with carbon nanotubes. The growth of carbon nanotubes can increase the specific surface area of ​​the electrode, improve the conductivity and ion transport performance of the electrode, etc. After the carbon source gas (such as one or more combinations of carbon monoxide, carbon dioxide, ethylene, acetylene, methane and propylene gas) is introduced into the fluidized bed, a decomposition reaction occurs under the action of the catalyst. Taking ethylene as the carbon source as an example, under the catalysis of catalysts such as silver, silver-based iron, silver-based cobalt, and silver-based nickel, the carbon-carbon double bonds in the ethylene molecules will break, and carbon atoms will gather on the catalyst surface and gradually grow to form carbon nanotubes. According to the principle of chemical vapor deposition, during the reaction process, the carbon source gas is continuously decomposed, and the carbon atoms are orderly arranged and grown under the guidance of the catalyst, and finally a carbon nanotube layer is formed on the current collector, thereby making an electrode.

[0046] In one embodiment, the carbon source is one or more combinations of carbon monoxide, carbon dioxide, ethylene, acetylene, methane and propylene gases.

[0047] In the present embodiment, carbon monoxide is a gas with strong reducing properties. In the chemical vapor deposition process, the carbon-oxygen bond in the carbon monoxide molecule can be broken under the action of a catalyst, and the carbon atoms are used to construct carbon nanotubes. Carbon monoxide is relatively active, and its reactivity enables it to participate in the growth reaction of carbon nanotubes under relatively low temperature and pressure conditions in the presence of a suitable catalyst (such as silver, silver-based iron, silver-based cobalt, silver-based nickel, etc.). Carbon dioxide, as a carbon source, releases carbon atoms for the growth of carbon nanotubes when reduced. Ethylene molecules contain carbon-carbon double bonds, and this unsaturated bond is easily broken under the action of a catalyst. Ethylene is a relatively ideal carbon source, which can provide enough carbon atoms and has high reactivity, and carbon nanotubes can be efficiently generated in the chemical vapor deposition reaction. Its double bond structure enables it to decompose and reorganize carbon atoms in a certain way when interacting with a catalyst, which is conducive to controlling the growth structure of carbon nanotubes, such as tube diameter and tube wall thickness. Acetylene is a highly active gas containing a carbon-carbon triple bond. The bond energy of its carbon-carbon triple bond is relatively low, and it is easy to break on the catalyst surface to release carbon atoms. When acetylene is used as a carbon source, it can quickly provide carbon atoms, which is conducive to the rapid growth of carbon nanotubes. In addition, due to its high activity, under some special reaction conditions (such as high temperature and high catalyst activity), carbon nanotubes with special structures can be generated, such as carbon nanotubes with high crystallinity or small diameter. Methane is the simplest organic compound, and its carbon-hydrogen single bond is relatively stable. However, under the action of high temperature and catalyst, methane can undergo a decomposition reaction to release carbon atoms for the growth of carbon nanotubes. The advantages of methane are that it has a wide range of sources and low cost, and it is a relatively economical carbon source choice. The propylene molecule contains a carbon-carbon double bond and a methyl group. This structural feature makes it have a certain reactivity during the reaction process and can provide a more complex carbon structural unit for the growth of carbon nanotubes. Under the action of the catalyst, propylene can generate carbon nanotubes through a variety of reaction pathways, and can have different effects on the structure and properties of carbon nanotubes.

[0048] In one embodiment, the chemical deposition method is a direct current electrodeposition method or a pulse electrodeposition method, which is not specifically limited in the present application.

[0049] Another embodiment of the present invention provides a solid-state battery, comprising an electrode prepared by any of the above-mentioned electrode preparation methods as a negative electrode, wherein the electrolyte of the battery is a solid electrolyte, and the negative electrode further comprises a negative electrode active material, wherein the negative electrode active material is metallic lithium.

[0050] In this embodiment, the present application preferably combines the in-situ growth method to generate carbon nanotubes on the current collector as a carrier of the negative electrode catalyst. The catalyst uses nanosilver element and / or silver-containing complexes at the bottom and top of the carbon nanotubes, which can synergistically induce lithium ions to be uniformly deposited on the surface and bottom of the carbon nanotube electrode. When the lithium ions are evenly distributed on the surface and inside of the electrode (inside and between the carbon nanotubes), there will be no local excessive lithium ion concentration, and uniform deposition can avoid the generation of local overpotential, thereby preventing lithium precipitation; at the same time, by designing and controlling the amount of lithium deposition not to exceed the maximum deposition capacity inside and between the carbon nanotubes, the entire electrode does not expand or shrink during the charge and discharge process, effectively limiting the expansion of lithium metal.

[0051] It should be noted that in-situ growth electrode refers to the process of growing electrode active materials with specific structures and functions directly on a substrate (such as a current collector) through chemical reactions, thereby preparing an electrode. The in-situ growth method is used as a method for preparing carbon nanotubes in this application, and is only implemented as a preferred embodiment. This application does not limit the use of other methods to prepare carbon nanotubes, as long as the catalyst is distributed at the bottom and top of the carbon nanotubes after growth.

[0052] The preparation process and performance of the present invention are described below with reference to some specific embodiments.

[0053] Example 1

[0054] 2g of silver was coated on the surface of the copper foil as a catalyst, and 98g of array carbon nanotubes were grown by chemical vapor deposition. The carbon nanotubes were 50um in length, and an electrode of in-situ grown carbon nanotube / copper foil composite was obtained.

[0055] Example 2

[0056] In this embodiment, the only difference from Embodiment 1 is that the length of the carbon nanotubes is 70 um.

[0057] Example 3

[0058] In this embodiment, the only difference from Embodiment 1 is that the catalyst is a silver-based iron catalyst.

[0059] Example 4

[0060] In this embodiment, the only difference from Embodiment 1 is that the catalyst is a silver-based cobalt catalyst.

[0061] Example 5

[0062] In this embodiment, the only difference from Embodiment 1 is that the catalyst is a silver-based nickel catalyst.

[0063] Comparative Example 1

[0064] Commercially available carbon nanotubes were used as the negative electrode active material (weight 80 g), and 14 g of styrene-butadiene rubber and 6 g of carboxymethyl cellulose were added and wet mixed in water to obtain a slurry with a solid content of 20%. The slurry was then coated on the surface of a copper foil and baked to form an electrode with a single-sided thickness of 50 um, which was then rolled to obtain the electrode.

[0065] Comparative Example 2

[0066] In this comparative example, the only difference from Example 1 is that the catalyst is an iron catalyst.

[0067] Comparative Example 3

[0068] In this comparative example, the only difference from Example 1 is that the catalyst is a cobalt catalyst.

[0069] Comparative Example 4

[0070] In this comparative example, the only difference from Example 1 is that the catalyst is a nickel catalyst.

[0071] Comparative Example 5

[0072] In this comparative example, the difference from Example 1 is that the catalyst is only distributed at the bottom of the carbon nanotubes, and the catalyst is an iron catalyst.

[0073] The electrodes obtained in the above Examples 1-5 and the comparative example were assembled into a solid-state battery with ternary NCM811 (Nickel-Cobalt-Manganese: nickel, cobalt, manganese ternary material system, 811 represents the molar ratio of nickel, cobalt, and manganese to be about 8:1:1), and energy density tests, 1C cycle life and attenuation tests were performed, and the battery was disassembled. The data obtained are shown in the following table:

[0074]

[0075]

[0076] From the test results in the above table, we can see that:

[0077] Compared with the comparative example, after testing, the examples 1-5 of the present application were disassembled and found to have no lithium deposition on the surface of the negative electrode of the battery. This is because the negative electrode in the present application has nanosilver catalysts and / or silver-containing complexes at the bottom and top of the carbon nanotubes. Taking catalyst silver as an example, silver has specific chemical properties and surface energy, which can affect the deposition process of lithium metal on the surface and bottom of the negative electrode of the carbon nanotube. During the battery charging process, lithium metal ions need to be deposited on the surface of the negative electrode, and the silver catalyst can provide suitable active sites. Since the silver catalyst is present at the bottom and top of the carbon nanotubes at the same time, the lithium metal ions can be uniformly reduced to lithium metal atoms at these sites, thereby achieving uniform deposition. The uniformly deposited lithium metal can prevent the local lithium metal concentration from being too high and causing lithium deposition.

[0078] The energy density of Example 2 of the present application is higher than that of other examples and comparative examples. This is because the catalyst can reduce the energy barrier required for the growth of carbon nanotubes, making the reaction easy to proceed, thereby promoting the large-scale generation of carbon nanotubes. Taller carbon nanotubes have more conductive channels and active sites, which are beneficial to the transmission of electrons and the storage and diffusion of lithium ions, thereby improving the energy density of the battery; the catalyst can promote the uniform distribution of carbon nanotubes in the electrode and avoid the occurrence of agglomeration. The uniform electrode structure is beneficial to the uniform distribution and transmission of charges, improving the utilization rate of the electrode, thereby improving the energy density of the battery.

[0079] Compared with the comparative example, the 10s maximum discharge power of Examples 1-5 of the present application is higher than that of the comparative example. This is because during the preparation process of the electrode of the present application, the density between the carbon nanotubes can be adjusted by coating, and the carbon nanotubes are completely oriented under fluidization, and their porosity can be adjusted. The carbon nanotubes of the present application can provide a more favorable channel for the diffusion of lithium ions in the carbon nanotubes and the electrodes. When the battery is discharged, the lithium ions can be deintercalated from the negative electrode faster and diffuse to the positive electrode through the electrolyte. Rapid lithium ion diffusion can better coordinate with electron transport to maintain the high speed of electrode reaction. For example, during high-rate discharge (such as high-current discharge within 10s), lithium ions can be supplied to the reaction interface in time, so that the reaction rate of the battery is accelerated, thereby increasing the discharge power of the battery. At the same time, the carbon nanotube negative electrode with a catalyst can reduce the activation energy of the electrode reaction. During the battery discharge process, the electrode reaction (such as the transfer of deintercalation electrons of lithium ions) needs to overcome certain energy barriers before it can proceed. The presence of a catalyst can reduce this obstacle, making the reaction more likely to occur and the reaction rate is accelerated. During the short-term discharge process of 10s, this fast reaction kinetics enables the battery to output more electrical energy per unit time, thereby increasing the maximum discharge power.

[0080] Compared with Examples 1 and 5, the number of cycles in which the SOH decays to 80% in the 1C cycle test is greater in Examples 1-5 and Comparative Examples 2-4 of the present application, because the catalyst located at the bottom and top of the carbon nanotubes can promote the carbon nanotubes to grow more uniformly, with a narrower tube diameter distribution and a more suitable length. The uniform structure makes the conductive network formed by the carbon nanotubes in the negative electrode more stable and efficient, and can better withstand the structural stress caused by the insertion and extraction of lithium ions during the cycle, reducing local stress concentration and damage caused by structural inhomogeneity, thereby delaying the decay of battery performance and increasing the number of cycles.

[0081] Compared with Comparative Examples 2-4, after testing, Examples 3-5 were disassembled and found to have no lithium deposition on the negative electrode surfaces of the batteries. This is because among silver and silver-containing composites, silver has higher conductivity and can provide a good electron transfer environment for the growth of carbon nanotubes, which is beneficial to promote the formation of carbon nanotubes. At the same time, the chemical properties of silver are relatively stable, and it is less likely to have side reactions during the discharge process of the battery, which can reduce the accumulation of lithium ions on the negative electrode surface. Therefore, no lithium deposition was found on the negative electrode surfaces of the batteries.

[0082] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. An electrode, characterized in that: The invention comprises a current collector and a carbon nanotube layer covering the current collector, wherein catalysts are distributed at the bottom and the top of the carbon nanotubes.

2. The electrode according to claim 1, characterized in that The catalyst comprises one or more selected from silver and a silver-containing complex.

3. The method for preparing an electrode according to claim 1, characterized in that: The carbon nanotubes are one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes and modified carbon nanotubes.

4. A method for preparing an electrode, characterized in that: The method for preparing the electrode according to any one of claims 1 to 3 comprises the following steps: S1: coating the catalyst on the current collector; S2: placing the coated current collector in a fluidized bed for fluidization; S3: introducing a carbon source into the fluidized bed to grow carbon nanotubes by chemical vapor deposition to produce the electrode.

5. The method for preparing an electrode according to claim 4, characterized in that: The carbon source is one or more combinations of carbon monoxide, carbon dioxide, ethylene, acetylene, methane and propylene gases.

6. The method for preparing an electrode according to claim 5, characterized in that: The chemical vapor deposition method is a direct current electrodeposition method or a pulse electrodeposition method.

7. A solid-state battery, characterized in that: The electrode according to any one of claims 1 to 3 is included as a negative electrode.

8. The solid-state battery according to claim 7, characterized in that: The electrolyte of the solid-state battery is a solid electrolyte.

9. The solid-state battery according to claim 7, characterized in that: The negative electrode further comprises a negative electrode active material, and the negative electrode active material is metallic lithium.

Citation Information

Cited By

  • Electrode and preparation method therefor, and solid-state battery

    WO2026103153A1